Development of modern immunization agent against bovine papillomavirus type 1 infection based on BPV1 L1 recombinant protein - Vrablikova, Alena; Brezani, Veronika; Psikal, Ivan; Fraiberk, Martin; Sebela, Marek; Fojtikova, Martina; Kulich, Pavel; Hezova, Renata; Masek, Josef (Frontiers in Veterinary Science, 2023)
Bovine papillomavirus type 1 L1 protein was produced in a baculovirus expression system and purified as virus-like particles (VLPs) by affinity chromatography using lectins. Morphological integrity of VLPs was confirmed by electron microscopy. Differences between two detected variants were deciphered by Mass Spectrometry of peptides (MALDI-TOF). Mice were immunized with purified VLPs in dose of 10 µg, 25 µg, or 50 µg in combination with 1% saponin and 15% alhydrogel per dose as adjuvants. Analysis of the humoral immune response revealed high titers of specific antibodies detected 3 weeks after the first immunization in all groups of animals. This was further significantly increased by the booster applied at 3 weeks after the first dose with the best immune response in a group of mice immunized by the largest dose of antigen. BPV1 L1 VLPs purified by affinity chromatography using lectins could be used for prophylactic immunization in veterinary medicine.